2018
DOI: 10.2224/sbp.6676
|View full text |Cite
|
Sign up to set email alerts
|

Consumer purchase intention of a cosmetic product after the Fukushima nuclear incident

Abstract: We examined the factors affecting consumer purchase intention of a cosmetic product after the Fukushima nuclear incident and the role of distinctiveness in postcrisis recovery. Through a 2-group experiment and structural equation modeling, we found that the incident did not affect the firm's reputation and brand image but it was perceived as a significant threat to health and product safety that consequently negatively affected purchasing intentions. Findings also showed that high distinctiveness is a valid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Results rarely seem to support the thesis of Kaswengi et al (2020) that the availability of income has a low influence on these purchasing decisions. The results, on the other hand, are closer to the conclusions of Hyun and Choi (2018), who affirm that the crisis negatively affects purchase intentions, and to those of Hassan et al (2015) which underline a direct relationship with economic crises.…”
Section: Hypothesis Tests and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Results rarely seem to support the thesis of Kaswengi et al (2020) that the availability of income has a low influence on these purchasing decisions. The results, on the other hand, are closer to the conclusions of Hyun and Choi (2018), who affirm that the crisis negatively affects purchase intentions, and to those of Hassan et al (2015) which underline a direct relationship with economic crises.…”
Section: Hypothesis Tests and Discussionsupporting
confidence: 71%
“…In other countries, research has shown that spending on cosmetics has not changed in times of recession (Kaswengi et al. , 2020; Khvatova and Thakur-Weigold, 2019; Hyun and Choi, 2018; Hassan et al. , 2015) or it has moved towards cheaper products (Le Roux, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, customers are more likely to show behavioral loyalty, such as repurchase intention, when they are exposed to and experience caring through marketing actions including CSR as a proactive strategy. Thus, these strategies have become more important because of the increase in the likelihood of traumatic events including both natural and anthropogenic disasters (Hyun and Choi, 2018).…”
Section: Traumatic Eventsmentioning
confidence: 99%
“…• Kriz türü, krizin neden kaynaklandığı sorusuna yanıt aramaktadır. Zira, kusurlu ürün krizleri doğal afet veya asılsız söylentiler gibi çok çeşitli sebeplere dayanabilmektedir (Hyun ve Choi, 2018). Bu açıdan kriz türü krizin öncülünü bağlı olarak şekillenmekte, tüketicilerin ve firmanın krize yönelik algı ve tutumları üzerinde etkili olabilmektedir (Coombs, 1998).…”
Section: Kusurlu üRün Krizlerinin Temelinde Yer Alan Karakteristik öZelliklerunclassified